PENGENALAN CUCI TANGAN SEJAK DINI PADA ANAK TAMAN KANAK TERHADAP PENCEGAHAN INFEKSI PARASIT USUS - hani risnawati (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2025)
Clean and healthy living behaviours are one of the most important factors in preventing and controlling basic diseases that can be taught to children (Asri, 2025). One simple but highly effective way to maintain children's health is through the habit of washing hands with soap (Smith et al., 2022). According to data from the World Health Organisation (WHO), washing hands with soap can reduce the risk of diarrhoea by up to 40% (WHO, 2022). This community service aims to increase knowledge and clean living habits through proper hand washing practices as an effort to prevent intestinal parasite infections from an early age in kindergarten children. The results of this community service show that kindergarten children's participation in healthy lifestyle activities, such as hand washing, can reduce the risk of intestinal parasite infections, especially at important times such as before eating, after using the toilet, or after playing (Siregar, 2024). This community service is expected to encourage children, parents, educators, and the community to be more active in introducing and implementing clean and healthy living behaviours. Thus, this activity is expected to improve children's health and development holistically and sustainably. Keywords: Handwashing, Infection Prevention, Kindergarten Children, PHBS